Novel human genome variants associated with alcohol use disorders identified in a Lithuanian cohort - Baronas, Karolis; Rančelis, Tautvydas; Pranculis, Aidas; Domarkienė, Ingrida; Ambrozaitytė, Laima; Kučinskas, Vaidutis (Acta medica Lituanica, 2018)
Background. Alcohol use disorder (AUD) is a chronic relapsing brain disease characterized by compulsive alcohol use, loss of control over alcohol intake, and a negative emotional state when not using (1). Abusive alcohol consumption directly affects a person’s physical and psychological health and social life. The World Health Organization has shown that Lithuania is a leading country in pure alcohol consumption in the world (2). The aim of this study is to find novel genome variants that are associated with the AUD in the Lithuanian cohort. Materials and methods. A case-control study included 294 individuals of Lithuanian ethnicity, who were divided into two groups based on their habits of alcohol use. Single nucleotide polymorphism array analysis was performed using Illumina HiScanSQ™ genome analyzer. Results. Our study showed that rs686141T>C variant in NALCN gene is more prevalent in the non-drinker group compared to the alcohol drinker group (relative allele frequency, respectively: 0.38 and 0.27, OR = 0.60 (CI 95% 0.37–0.98), p = 0.0408). Meanwhile, rs6354C>A, in SLC6A4 gene, variant’s genotype distribution showed statistically significant difference between the non-drinker and alcohol drinker group (distribution of genotypes in the case group: 9/72/172 (CC/CA/AA) and in the control group: 5/7/29, p = 0.0264). Conclusion. We analyzed 23 genes associated with AUD and identified two novel genome variants (rs686141T>C and rs6354C>A). The study shows that genome analysis is an important tool for AUD research. The results supplement the known information about genes associated with AUD.
Keywords: Alcohol Use Disorder; Illumina HiScanSQ; genotyping; NALCN; SLC6A4